Working across Professional Boundaries - Atkinson, Adele; Start, Kath (Proceedings of the International Conference on Networked Learning, 2002)
As an individual matures, their self-concept matures from dependence to self-direction (Knowles, 1990). Strategies to foster self-directedness should aim to progressively decrease dependence on the educator, foster decision making and facilitate the application of theory to practice (Mezirow, 1981;Knowles, 1990). Problem based learning is one such strategy. It is student-centred and attempts to replicate issues that students see in practice (Amos and White, 1998).